CULTURAL UNTRANSLATABILITY: A STUDY ON THE RAINBOW TROOPS - Nur Utami Sari'at Kurniati (Celt: A Journal of Culture, English Language Teaching & Literature, 2014)
The notion of translatability is possibly done with the extent to which meaning can still be adequately conveyed across languages. For this to be feasible, meaning has to be understood not only in terms of what the source text contains, but also in terms of target audience and purpose of translation. In linguistic untranslatability, the functionally relevant features include some which are in fact formal features of the language of the source language text. If the target language has no formally corresponding feature, the text, or the item, is (relatively) untranslatable. What appears to be a quite different problem arises, however, when a situational feature, functionally relevant for the source text, is completely absent in the culture of target language. As culture has something to do with the concept, source language texts and items are more or less translatable rather than absolutely translatableoruntranslatable. An adaptation, then, is a procedure whereby the translator replaces a term with cultural connotations, where those connotations are restricted to readers of the original language text, with a term with corresponding cultural connotations that would be familiar to readers of the translated text. Translating such culturally untranslatable items entails profound knowledge on both source and target cultures. Most cases in this particular work are solved by keepingcultural terms in the source language text, with or without explanation. Ecological, social, and religious culture terms undergo the process most frequently.